Cathodic electrochemical determination of furfural in sugarcane bagasse using an electrode modified with nickel nanoparticles - Da Silva, José Luiz [UNESP]; Beluomini, Maísa Azevedo [UNESP]; Ramos Stradiotto, Nelson [UNESP] (Royal Society of Chemistry (RSC), 2017)
In this work, analytical methods were developed for the cathodic determination of furfural in sugarcane bagasse by electroanalytical techniques using a glassy carbon electrode modified with nickel nanoparticles. The methods were developed based on linear sweep voltammetry (LSV), square wave voltammetry (SWV) and differential pulse voltammetry (DPV). The developed analysis methods presented a limit of detection between 2.5 × 10-6 (DPV) and 4.9 × 10-5 mol L-1 (LSV). The amperometric sensitivity was of the order of 10-2 A mol-1 L-1. The recovery study showed that the developed methods have good accuracy and repeatability, with a recovery of 98.4 and 103.7% for LSV and SWV, respectively. The proposed methods were successfully applied to sugarcane bagasse samples and an average furfural concentration of 12.9 ± 0.2 g kg-1 was found in the sugarcane bagasse.